Neue Proctotrupoidea aus dem Baltischen Bernstein. - Szabó, Janoš; Oehlke, Joachim (Contributions to Entomology = Beiträge zur Entomologie, 1986)
From the baltic-amber five new species were discribed. The species belong to recent genera of famelies Ceraphronidae, Proctotrupidae, Scelionidae and Diapriidae. Nomenclatural Actsbalticus Szabó & Oehlke, 1986 (Cinetus), spec. n.koggeauxilliarius Szabó & Oehlke, 1986 (Cryptoserphus), spec. n.ilonkae Szabó & Oehlke, 1986 (Idris), spec. n.pseudocarinatus Szabó & Oehlke, 1986 (Lagynodes), spec. n.renatae Szabó & Oehlke, 1986 (Macroteleia), spec. n.